Effect of Remote Ischemic Preconditioning in the Elderly Patients With Coronary Artery Disease With Diabetes Mellitus Undergoing Elective Drug-Eluting Stent Implantation. (September 2014) - Xu, Xiaohan; Zhou, Yujie; Luo, Shengjie; Zhang, Weijun; Zhao, Yingxin; Yu, Miao; Ma, Qian; Gao, Fei; Shen, Hua; Zhang, Jianwei
There is conflicting evidence regarding the effectiveness of remote ischemic preconditioning (RIPC) in patients undergoing elective percutaneous coronary intervention (PCI). Therefore, we prospectively enrolled elderly patients with coronary heart disease (CHD) with diabetes mellitus (DM) undergoing elective drug-eluting stent (DES) implantation. They were randomized to receive RIPC within 2 hours before PCI (n = 102) or not (controls, n = 98). Baseline clinical characteristics were similar between the 2 groups. Despite a trend toward decline, the median high-sensitivity cardiac troponin I (hscTnI) level ( P = .256) and the incidence of myocardial infarction (MI) type 4a ( P = .106) in the RIPC group 16 hours after PCI procedure was not significantly different from the control group. The RIPC could attenuate the release of a myocardial biomarker but failed to show a significant effect on hscTnI level or MI type 4a incidence after PCI procedure in elderly patients with CHD having DM undergoing elective DES implantation.